Case Report: Ruptured Middle Cerebral Artery Aneurysm With Intrasylvian Hematoma Successfully Treated by Coil Embolization and Minimally Invasive Puncture and Drainage - Li, Zhen; Hu, Quan; Zhao, Li; Huang, Huayun; Zhang, Shizhong; Zheng, Limin; Wang, Guojun (Frontiers in Neurology, 2021)
Up to one-third (12–35%) of patients with aneurysmal subarachnoid hemorrhage experience intracerebral hematoma. Ruptured middle cerebral artery (MCA) aneurysm with hematoma is usually accompanied by progressive cerebral swelling with poor outcomes; however, it can be successfully treated by coil embolization and minimally invasive puncture and drainage. From February 2012 to March 2019, six surgeries for ruptured MCA aneurysms with intrasylvian hematoma were performed at our clinic. All patients had intracranial hematomas of <30 ml and GCS scores >8. The patients were treated by coil embolization and minimally invasive puncture and drainage. The aneurysms in all patients were completely embolized and the hematomas were mostly removed by minimally invasive puncture. The Glasgow outcome scale (GOS) scores of all patients were more than 4 at discharge when they discharged. Coil embolization and minimally invasive puncture and drainage are viable treatments for ruptured MCA aneurysms with hematomas, especially if the patient is too old, in a complicated state to undergo craniotomy, is unwilling to undergo craniotomy, or is at a greater risk of bleeding 3 days after surgery.